Invocation of the educational ombudsman as a legal instrument for the protection of non-proprietary personal rights - Voloshyn, H.; Волошин, Г. (Visegrad Journal on Human Rights. - 2024. - № 2. - P. 122-126, 2024)
У цій науковій статті досліджується застосування самозахисту як правового механізму, розробленого спеціально для захисту громадянських прав учасників у навчальних закладах, з особливим акцентом на неповнолітніх. Дослідження ретельно окреслює операціоналізацію самооборони, заглиблюючись у її процедурні тонкощі та різноманітні контексти, в яких її можна застосовувати в освітньому середовищі. Це дослідження допомагає з’ясувати нюанси за допомогою якого люди можуть відстоювати свої права в освітньому контексті, підкреслюючи як можливості та обмеження необхідної оборони як правового заходу захисту. Розширюючи рамки аналізу, у статті також розглядається роль освітніх омбудсменів у ведення судових спорів. Запропоновано всебічний огляд функціонального впливу та процедурних ролей, які ці омбудсмени відіграють у правових рамках, що регулюють освітні заклади. Цей сегмент дослідження оцінює, як освітні омбудсмени сприяють вирішенню конфліктів і дотриманню правових стандартів, тим самим посилюючи захист прав студентів.

This scholarly paper investigates the application of self-defense as a legal mechanism designed specifically to safeguard the civil rights of participants within educational settings, with a special focus on minors. The study meticulously outlines the operationalization of self-defense, delving into its procedural subtleties and the varied contexts in which it can be applied within educational environments. This exploration helps elucidate the nuanced ways through which individuals can assert their rights in educational contexts, highlighting both the potential and the limitations of self-defense as a protective legal measure. Expanding the scope of the analysis, the paper also examines the role of educational ombudsmen in navigating judicial disputes. It offers a comprehensive review of the functional impacts and procedural roles these ombudsmen play within the legal frameworks governing educational institutions. This segment of the study assesses how educational ombudsmen contribute to the resolution of conflicts and the enforcement of legal standards, thereby enhancing the protection of students’ rights. Incorporating a robust comparative analysis, the research extends into the international arena, exploring the praxis of educational ombudsmen across different jurisdictions. It assesses the legislative outcomes of their involvement in judicial proceedings and scrutinizes how these vary across diverse legal systems. This comparative approach not only underscores effective strategies but also identifies best practices that could be emulated to bolster the legal protection of educational rights through judicial processes. By synthesizing theoretical frameworks with empirical research, this paper contributes significantly to the scholarly discourse on educational law and civil rights protection. It critically examines the intersection of education, law, and civil rights, proposing necessary refinements to existing legal mechanisms and suggesting new areas for in-depth research. These recommendations aim to enhance the effectiveness of educational ombudsmen and to ensure more robust legal protections for all participants within the educational sector.

В этой научной статье исследуется применение самообороны как правового механизма, специально разработанного для защиты гражданских прав участников в образовательных учреждениях, с особым акцентом на несовершеннолетних. В исследовании подробно описывается операционализация самообороны, вникая в ее процессуальные тонкости и разнообразные контексты, в которых она может применяться в образовательных учреждениях. Это исследование помогает прояснить тонкие способы, с помощью которых люди могут отстаивать свои права в образовательных учреждениях, подчеркивая как потенциал, так и ограничения самообороны как защитной правовой меры. Расширяя сферу анализа, в статье также рассматривается роль образовательных омбудсменов в разрешении судебных споров. В ней предлагается всесторонний обзор функциональных воздействий и процессуальных ролей, которые эти омбудсмены играют в правовых рамках, регулирующих образовательные учреждения. В этой части исследования оценивается, как образовательные омбудсмены способствуют разрешению конфликтов и обеспечению соблюдения правовых стандартов, тем самым усиливая защиту прав студентов.
Keywords: освітній омбудсмен; права студентів; позаюрисдикційний захист прав; правові механізми в освіті; судові спори в освіті; Educational ombudsman; students’ rights; non-jurisdictional protection of rights; legal mechanisms in education; judicial disputes in education; образовательный омбудсмен; права студентов; неюрисдикционная защита прав; правовые механизмы в образовании; судебные споры в образовании